Factors Influencing Stope Hanging Wall Stability and Ore Dilution in Narrow-Vein Deposits: Part 1 - Abdellah, Wael R. Elrawy; Hefni, Mohammed A.; Ahmed, Haitham M. (Geotechnical and geological engineering, 2020)
The sublevel open stope method is widely practiced in many Canadian mines when extracting thin tabular orebodies. This method is used as an alternative to sublevel caving when ore dilution (contamination of ore by waste rock) is an issue and where fairly competent rock exists. Dilution and instability at the stope hanging wall (HW) can significantly increase mining operation costs. Dilution reduces the ore grade and increases the amount of material that needs to be extracted and transported to the mill. Stope instability among the many factors that strongly affect ore dilution and stope stability, this paper examines in-stress regimes and depth of stope undercutting of the access drift using the Mohr–Coulomb elastoplastic failure evaluation criterion and RS 2D software. Stope HW stability was assessed in terms of depth of the relaxation zones at the center of the stope HW, the extent of yield or failure zones, and deformation contours. Results reveal that the stability of the stope HW significantly deteriorates when in situ stress regimes and depth of stope undercutting increase. Conversely, the depth of relaxation zones and the extent of yield regions increase when the in situ stress and depth of stope undercutting increase. However, the depth of stope undercutting does not influence deformation developments (e.g., deformations only affected by the change in the in situ stress ratio).